PELATIHAN PACKAGING YANG SUSTANABLE DAN RAMAH LINGKUNGAN DI UKM KAMPUNG JOYORAHARJAN SURAKARTA - Murni, Endri Sintiana; Handayani, Endang Sri; Fuad, Figur Rahman (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
Abstract Joyoraharjan village is a densely populated village. This densely populated village has a creative village empowerment program that supports the Surakarta City tourism awareness program. However, the existing potential needs to be supported by efforts to support the products contained in the village to become selling power and able to boost the residents' economy. The packaging for the products in Joyoraharjan Village has not been able to attract tourists to buy their products. So that the packaging training is held. Training on product packaging in Joyoraharjan Village as a tourism village has been started and in its manufacture through several activities both making logos and making packaging. The final result of the packaging training using printing techniques is in the form of several packaging models that are environmentally friendly and sustainable. Product packaging is made with environmentally friendly and easy-to-obtain manufacturing materials so that they are able to independently package their superior products. Abstrak Kampung Joyoraharjan merupakan kampung padat penduduk. Kampung dengan kondisi lingkungan padat penduduk ini memiliki program pemberdayaan kampung kreatif yang mendukung program sadar wisata Kota Surakarta. Namun, dari potensi yang ada perlu didukung dengan adanya upaya dalam mendukung produk-produk yang terdapat di kampung tersebut menjadi berdaya jual dan mampu mendongkrak perekonomian warga. Packaging pada produk yang terdapat di Kampung Joyoraharjan belum dapat menarik minat wisatawan dalam membeli produknya. Sehingga diadakannya pelatiahan packaging. Pelatihan packaging produk di Kampung Joyoraharjan sebagai kampung wisata mulai dilakukan dan dalam pembuatannya melalui berberapa kegiatan baik membuat logo dan membuat packaging. Hasil akhir dari pelatihan pembuatan packaging dengan teknik cetak ini berupa beberapa model packaging ramah lingkungan dan suistanable. Packaging produk dibuat dengan bahan pembuatan yang ramah lingkungan dan mudah didapatkan sehingga mampu untuk membuat packaging produk-produk unggulan mereka secara mandiri.